Stability and deformation of underground excavation in rocks - Foo, Jason Zhi Pin. (2012)
The study of underground excavations in rocks is at its early stages. To build and maintain underground rock tunnel requires meticulous and thoughtful designs in the process of excavation. Such process includes the method of excavation and setting up the support structure for the rock tunnel.